2016
DOI: 10.1016/j.scitotenv.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

On the potentials of multiple climate variables in assessing the spatio-temporal characteristics of hydrological droughts over the Volta Basin

Abstract: Multiple drought episodes over the Volta basin in recent reports may lead to food insecurity and loss of revenue. However, drought studies over the Volta basin are rather generalised and largely undocumented due to sparse ground observations and unsuitable framework to determine their space-time occurrence. In this study, we examined the utility of standardised indicators (standardised precipitation index (SPI), standardised runoff index (SRI), standardised soil moisture index (SSI), and multivariate standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 80 publications
1
38
0
Order By: Relevance
“…Obviously, the observed extremes in West African rainfall (especially the Guinea Coast) is likely to increase owing to the strong impacts of climate variability, environmental changes, influence of tropical Atlantic sea surface temperature (SST) anomalies, and the nature of West African Monsoon, which is largely controlled by interactions between continental surfaces and the oceans (see, e.g., Rodríguez‐Fonseca et al, ; Losada et al, ; Redelsperger and Lebel, ; Polo, Rodríguez‐Fonseca, Losada & García‐Serrano, ; Redelsperger et al, ). The overarching outcomes of a plethora of related studies in West Africa (see, e.g., Ndehedehe, Awange, Corner, Kuhn & Okwuashi, ; Diatta and Fink, ; Nicholson, ; Paeth et al, ; Bader and Latif, ; Joly and Voldoire, ; Losada et al, ; Ali and Lebel, ; Giannini et al, ; Reason and Rouault, ), be it region‐specific or basin scale, overwhelmingly agree on the roles of climatic variations through changes in the global oceans, mesoscale convective systems, and indices of climate variability (e.g., ENSO, Atlantic Multi‐decadal Oscillation [AMO], PDO, etc.) on precipitation patterns and other water fluxes (e.g., stream flow).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the observed extremes in West African rainfall (especially the Guinea Coast) is likely to increase owing to the strong impacts of climate variability, environmental changes, influence of tropical Atlantic sea surface temperature (SST) anomalies, and the nature of West African Monsoon, which is largely controlled by interactions between continental surfaces and the oceans (see, e.g., Rodríguez‐Fonseca et al, ; Losada et al, ; Redelsperger and Lebel, ; Polo, Rodríguez‐Fonseca, Losada & García‐Serrano, ; Redelsperger et al, ). The overarching outcomes of a plethora of related studies in West Africa (see, e.g., Ndehedehe, Awange, Corner, Kuhn & Okwuashi, ; Diatta and Fink, ; Nicholson, ; Paeth et al, ; Bader and Latif, ; Joly and Voldoire, ; Losada et al, ; Ali and Lebel, ; Giannini et al, ; Reason and Rouault, ), be it region‐specific or basin scale, overwhelmingly agree on the roles of climatic variations through changes in the global oceans, mesoscale convective systems, and indices of climate variability (e.g., ENSO, Atlantic Multi‐decadal Oscillation [AMO], PDO, etc.) on precipitation patterns and other water fluxes (e.g., stream flow).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other parts of the world, rainfall and hydro‐climatic conditions in West Africa are influenced by ENSO and a number of other global climate teleconnections (AMO, Indian Ocean Dipole [IOD], etc. ; see, e.g., Ndehedehe, Agutu, Okwuashi, & Ferreira, ; Ndehedehe, Awange, Corner, et al, ; Diatta & Fink, ; Molion & Lucio, ; Paeth et al, ; Bader & Latif, , ; Giannini, Saravanan, & Chang, ; Nicholson, Some, & Kone, ; Nicholson, , and the references therein). These climate teleconnections result in extreme hydrological conditions and intensification of the water cycle, all of which impact on TWS in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (see, e.g. Ndehedehe et al, 2016c;Diatta and Fink, 2014;Nicholson et al, 2000;Janicot et al, 1996) have suggested a possible relationship between climate indices (e.g. Atlantic multi-decadal oscillation-AMO, Atlantic meridional mode-AMM, El-Niño Southern Oscillation-ENSO, Pacific Decadal Oscillations-PDO) and rainfall extremes over WA.…”
Section: Introductionmentioning
confidence: 99%
“…However, ENSO is not the only climate factor influencing the precipitation anomalies. Other large-scale ocean-atmosphere oscillations such as Indian Ocean dipole (IOD) and Pacific Decadal Oscillation (PDO) might also be connected with the temporal evolutions of precipitation in this basin [16].…”
Section: Connection With Precipitationmentioning
confidence: 99%
“…Ahmed et al [11] and Moore and Williams [13] have attributed this to the impoundment of water by Akosombo Dam. Ndehedehe et al [16] examined space-time characteristics of droughts over the VRB using GRACE data and multiple drought indices. In addition, studies of VRB water balance have been undertaken using a variety of models and data (e.g., [17][18][19]).…”
Section: Introductionmentioning
confidence: 99%